A Phenomenological Study on Islamic Parenting in Introducing Worship to Early Childhood at Al-Munawarah Kindergarten - Loeziana Uce; Hayati Hayati; Nurbayani Nurbayani; Cut Nya Dhin; Niza Rusita Maizanti (Khazanah Pendidikan Islam, 2025)
Parenting patterns for early childhood are very important because they affect the child's spiritual development. Good parenting patterns will have a positive impact on the child's growth. This study aims to see and analyze Islamic parenting patterns with the introduction of worship to children aged 4-5 years at Al-Munawarah Kindergarten. By using phenomenological research through a qualitative approach, it is hoped that this study will be able to describe the subjective experiences of individuals or groups in the context of Islamic parenting patterns. The results of this study are that (1) The model of parental role models as an illustration of early childhood in performing worship that children will prefer to imitate their parents or people around them. Because parents and teachers are models for them and children like to imitate and emulate them. In teaching role models, it is divided into two, namely consistency in worship and teach worship to young children directly. (2) Pattern fostering worship as religious tolerance for early childhood that parents at Al Munawarah Kindergarten who demonstrate tolerant and respectful attitudes. Parents give each other respect to their friends or neighbors so that early childhood children see firsthand the teachings given by their parents. Parents also give advice that focusing on worship is important and maintaining friendships of different religions is also important. In this case, religious differences can help their children develop the same attitude. Education carried out by parents at home, such as talking about diversity, can strengthen the values of tolerance. So, Islamic parenting is implemented through the example of parents/teachers in worship and fostering tolerance by showing respect in daily interactions, including towards followers of other religions.